Integrasi Latihan Fisik Dan Kognitif Dalam Meningkatkan Performa Pemain Futsal - Sarno Sarno (FKIP UNSULTRA, 2026)
Futsal is a team sport characterized by high physical and cognitive demands, requiring players to perform high-intensity activities while processing game information rapidly. This study aimed to analyze the integration of physical and cognitive training in improving futsal players' performance through a literature review. The study employed a narrative-descriptive literature review approach. Relevant literature was searched through PubMed, Scopus, Web of Science, and Google Scholar using keywords related to physical training, cognitive training, perceptual-cognitive training, small-sided games, brain endurance training, and futsal performance. The selected literature was analyzed according to five main themes: physical training and explosive performance, cognitive training and decision-making, small-sided games as an integrative training approach, brain endurance training, and physical-cognitive integration for performance enhancement. The findings indicate that physical training contributes to improvements in sprint performance, agility, strength, power, and repeated sprint ability. Cognitive training supports perception, anticipation, attention, and decision-making abilities. Meanwhile, integrative approaches such as small-sided games, situational training, virtual reality, and brain endurance training provide simultaneous physical and cognitive stimuli that more closely resemble actual match demands. Integrating these components enables players to maintain movement quality and decision-making performance under pressure and fatigue. Therefore, an integrated physical-cognitive training approach can serve as a comprehensive strategy for futsal development, supporting improvements in players' physical, cognitive, technical, and tactical performance.